MSADBDFPHDTK MIKROPIGMENTASI SULAM ALIS DAN BIBIR DALAM FIKIH: PRINSIP HAJIZ DAN TAGHYIR KHALQILLAH: Definisi dan Klasifikasi Fikih, Kajian Ilmiah Micropigmentation,Analisis Fikih Prinsip Hajiz (Penghalang Air) Dalam Praktik Tharah dan Penerapannya Pada Sulam Atau Tato Modern,Analisis Fikih Prinsip Taghyir Khalqillah (Mengubah Ciptaan Allah), - Oktaviani, Ria; Reni Kurniawati; Nur Aidah Fauziah; Thahir Maloko; Achmad Musyahid (STIS MIFTAHUL ULUM LUMAJANG PRESS (STISMU PRESS), 2026)
This study discusses the practice of eyebrow and lip embroidery micropigmentation from the perspective of Islamic Jurisprudence on the principle of hajiz (water barrier) in thaharah and the concept of taghyir khalqillah (change of Allah's Creation). The phenomenon of the increasing use of semi-permanent beauty procedures among Muslim women has raised legal debates because it is often equated with the practice of permanent tattoos which are prohibited in the hadith. This study aims to discuss the legal status of eyebrow and lip embroidery by considering the normative fiqh aspects and dermatological scientific explanations regarding the micropigmentation technique. The research method used is qualitative research with a juridical-normative approach through a literature study of classical and contemporary fiqh literature, fatwas of religious institutions, and related medical studies. The results of the study show that micropigmentation differs substantially from permanent tattoos because the pigment is implanted superficially and is semi-permanent, so it does not always meet the criteria for hajiz which invalidates wudu. From the aspect of taghyir khalqillah, this practice cannot be considered absolutely haram, but depends on the purpose, level of change and the impact it causes. This study concludes that the law on eyebrow and lip embroidery is ijtihadi and contextual, depending on the purpose, level of change and impact caused and requires caution by considering sharia principles and developments in modern beauty technology. Keywords : Micropigmentation, eyebrow and lip embroidery, hajiz, taghyir khalqillah, contemporary fiqh.